Mapping research frontiers in microplastics-induced oxidative stress: a bibliometric analysis (2010–2024) - Yang, Yadi; Chen, Yin; Gao, Yin; Jin, Yuyang; Xu, Fang (Frontiers in Environmental Science, 2025)
Introduction: Microplastics exposure is increasingly recognized as a significant contributor to oxidative stress, prompting growing concerns about potential human health impacts. This study aimed to systematically analyze emerging research trends and key thematic areas related to oxidative stress induced by microplastics, providing insights that could inform effective antioxidant-based interventions.Methods: A total of 1,820 relevant articles published between 2010 and 2024 were retrieved from the Web of Science Core Collection. Bibliometric techniques, including Latent Dirichlet Allocation (LDA), keyword co-occurrence analysis, and temporal regression modeling, were employed to analyze thematic structures, keyword relationships, and research development patterns.Results: Analysis revealed a notable increase in research volume over the study period, particularly highlighting health risk assessments and molecular mechanisms as focal points. Oxidative stress was identified as a central mediator linking inflammation, gut microbiota alterations, and apoptotic pathways. Clustering analyses demonstrated significant interdisciplinary connections, underscoring complex interactions across multiple biological systems. Additionally, temporal analysis indicated a recent surge in studies emphasizing health risk evaluations and potential antioxidant interventions.Discussion: The findings emphasize oxidative stress as a crucial mechanism in microplastics-induced toxicity, suggesting dietary antioxidants, such as zinc and N-acetylcysteine, could mitigate associated health risks. This study provides valuable perspectives to guide future research directions and public health strategies aimed at addressing microplastics exposure.